STYLISTIC DEVICES FOR EXPRESSING EMOTIONS IN "OLIVER TWIST" BY CHARLES DICKENS - Abdurazzoqova Kamola (Ustozlar uchun, 2025)
This article explores the main stylistic devices employed by Charles Dickens in "Oliver Twist" to express emotions. By analyzing the use of symbolism, irony, and dialogue, this study aims to highlight how these devices contribute to the emotional depth of the narrative and enhance the reader's engagement with the text.